Gender, Acculturation and Alcohol Use among Latina/o Adolescents: A Multi-Ethnic Comparison - Wahl, Ana-María González (2010)
This is the first study to examine the relationship between acculturation and alcohol use by gender and ethnicity using a nationally representative sample of Hispanic and non-Hispanic white adolescents. Specifically, we use data from the National Longitudinal Study of Adolescent Health (Add Health) to explore alcohol use and binge drinking for a sample that includes 6792 non-Hispanic whites, 910 Mexican Americans, 290 Cuban Americans, and 336 Puerto Ricans. Bivariate results reveal significant gender differences in alcohol use among first generation Mexican American, first generation Puerto Rican, and second generation Cuban American adolescents. In addition, these results indicate binge drinking differs significantly by gender among first generation Mexican American, first generation Cuban American, third plus generation Puerto Rican, and third plus generation non-Hispanic white adolescents. Multivariate logistic regression reveals that gender also moderates the effect of acculturation as well as ethnicity on alcohol use and abuse. Among both males and females, first generation immigrants are significantly less likely than third plus generation immigrants to use alcohol and binge drink while selective acculturation significantly reduces the odds of both behaviors. However, the effects of immigrant generation and selective acculturation on binge drinking are larger for females. Further, the trajectories that alcohol use and binge drinking follow with acculturation differ significantly by gender and ethnicity. These results reaffirm the need to further develop theoretical models and intervention strategies that are both gender-specific and culturally-specific, targeting high risk groups in particular in these efforts.